The influence of the big five personality factors on students attitude towards the aged in Ibadan (2012)
Ageism remains a threat to successful aging. In 1950, the world housed an estimated 205 million older persons, 606 million in 2000, 701 million in 2007, it is however expected to double 1.2 billion by 2025 and triple by 2050 respectively. This unprecedented growth of the aged is causing widespread concern. One of the world poorer countries such as Nigeria will account for most of the increase in elderly population from 1980 thru 2000 to the year 2020. The attitude of the society towards the elderly becomes more negative, and the elderly are devalued. This survey research study investigated the influence of the big five personality factors (extraversion, agreeableness, conscientiousness, neuroticism and openness to experience] on students' attitude towards aging population in Ibadan, Oyo State, Nigeria. It will also investigate the roles of some demographic variables (e.g., age, gender, ethnicity, religion and level of study) on students’ attitude towards the adding population. The study settings were the Davidoff Idia and Queens's undergraduate halls of the University of Ibadan. In addition, the rest in the faculty of the Social Science were equally used. The study used the ex-post facto design where the participants were conveniently sampled. A sample of one hundred and fifty students' comprising of 64 males and 86 females was participated in the study, the participants age ranged from 17% and 32 years old, include 64(42.7%>) males and 86(57.3%) females. Twenty-two (14.7%) of the students were in 100 level, 43(28.7%) were in 200 level, 64(42.7%)) were 300 level while, 21(14%o) were in 400 level. One hundred and forty (93.3%>) of the participants were single, while only 10(6.7%>) were married. Their religious affiliation shows that 105 (70%>) were Christians, while 45(30%>) were Islamic students. Hypothesis one was supported t (148) = - 1.424, P <. 05. Hypothesis two was supported t (148) = -.925, P < 05. Hypothesis three was supported t (148) = -2.985, P <. 01. Hypothesis four supported t (148) = .577, P <. 05. Finally, the fifth hypothesis was partial supported F (5,145) = 6.049, P <.001. In conclusion, the findings of this result are indeed quite suitable for the development of an intervention package to address the aging population issues among students and youths alike in Nigeria